2008
DOI: 10.1590/s0037-86822008000700012
|View full text |Cite
|
Sign up to set email alerts
|

Soroprevalência do teste ML Flow em contatos de hanseníase de Minas Gerais

Abstract: Leprosy is a public health problem in Brazil. Epidemiological control actions are based on the diagnosis and treatment of leprosy patients and household contact surveillance. Serological tests for leprosy could identify from among the contacts those at greater risk of developing leprosy in the future. ML Flow was administered to 2,840 household contacts of new leprosy cases diagnosed from October 2002 to March 2004, in State of Minas Gerais. ML Flow was positive in 20.5% of leprosy contacts, with high seroposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 15 publications
6
16
0
2
Order By: Relevance
“…23 Interestingly, there was no difference in terms of seropositivity and sex whereas in the literature, there are some discordant results. 8,18,24 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Interestingly, there was no difference in terms of seropositivity and sex whereas in the literature, there are some discordant results. 8,18,24 …”
Section: Discussionmentioning
confidence: 99%
“…Positivity varies from 15.6% 19 20.5% 18 and 28.6%. 5 As reported, the risk of seropositive contacts developing leprosy can be six times higher compared with the negative samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,14 Nevertheless, it is different in other studies where a predominance of male contacts was observed. 16,17 This predominance in the study may be associated with the fact that in the municipality of São Luís the population is composed mostly of women. 15 During the evaluation of the relation of the degree of kinship of the contact with the index case, the findings of this research demonstrate a higher frequency of firstdegree consanguineous, followed by non-consanguineous relatives, matching the results pointed out in other studies.…”
Section: Discussionmentioning
confidence: 86%
“…O PGL-I identifica pacientes do polo virchowiano que induz à produção de grandes quantidades de anticorpos ou imunoglobulinas do tipo IgM, conferindo soropositividade de 80 a 100%; porém, entre pacientes do polo tuberculoide, ocorre fraca produção de anticorpos IgM ou baixos níveis de detecção, conferindo soropositividade de 30 a 60% 17,18,19,20 .…”
Section: Aspectos Gerais E Combate à Hanseníaseunclassified